Effect of carbon types on the generation and morphology of GaN polycrystals grown using the Na flux method. Issue 5 (8th December 2014) - Liu, Zongliang; Ren, Guoqiang; Shi, Lin; Su, Xujun; Wang, Jianfeng; Xu, Ke
Abstract : The effect of different carbon types, including carbon nanotubes, active carbon, graphene, graphite, and ordered mesoporous carbon, on the suppression of polycrystal generation and morphology of GaN polycrystals grown by the Na flux method has been studied for the first time. Abstract : The effect of different carbon types, including carbon nanotubes, active carbon, graphene, graphite, and ordered mesoporous carbon, on the suppression of polycrystal generation and morphology of GaN polycrystals grown by the Na flux method has been studied for the first time. The results of GaN growth by adding different purity graphite indicate that graphite with higher purity is better than lower purity ones at suppressing polycrystal generation. Furthermore, by comparing the different types of carbon, it is found that the suppression effect increases in the following order: carbon nanotubes, active carbon, graphene, graphite, and ordered mesoporous carbon, accompanied by the evolution of morphology. First-principles calculation and specific surface area measurement show that the C–N bond energy in carbon plays a key role in suppressing the polycrystals, rather than the specific surface area of carbon. A mechanism of C–N bonding in Na–Ga melts has been proposed to illustrate the difference in suppressing polycrystal generation and morphology evolution.